Evaluando las condiciones de racionalidad y plausibilidad en la valoración de conservar la biodiversidad de un país megabiodiverso: el caso del Manu en Perú - Dávila, José (2023)
According to NOAA, the results of an economic valuation are applicable as public policy if they fulfill two conditions: rationality and plausibility. In this study, we carried out the valuation of biodiversity conservation in Manu National Park in Peru (a megabiodiverse country), based on three representations: species, habitat and functionality. We identify sensitivity to scope in most of the attributes used. When we add socioeconomic characteristics, we identify that gender and salary levels affect preferences. Our total analysis shows that number of threatened plant species and functionality better fulfill both conditions.